2001
DOI: 10.1111/j.1749-6632.2001.tb03713.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Human T Cell Lymphotropic Virus Type I Tax in the Development of Cutaneous T Cell Lymphoma

Abstract: Although it has been well established that the human T cell lymphotropic virus type I (HTLV‐I) causes adult T cell leukemia/lymphoma (ATLL) in regions of the world where this virus is endemic, its role in the pathogenesis of cutaneous T cell lymphoma (CTCL) in the Western world has been less well established. Most patients with CTCL are negative for antibodies to the structural proteins of HTLV‐I, and thus a causative role for this virus is usually dismissed. However, the Tax sequence of HTLV‐I has been found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 33 publications
0
8
1
2
Order By: Relevance
“…Most patients with CTCL are negative for antibodies to the structural proteins of HTLV-I, and thus a causative role for this virus is usually dismissed. However, numerous studies have found HTLV-I-related proviral tax sequence or deleted proviruses in tumor samples from CTCL patients [27][28][29][30][31][32][33][34]. Recently a study on the northeastern coast of Brazil found HTLV-I integrated proviral sequences by southern blot in several mycosis fungoides-like cutaneous lymphomas, and CD30 + largecell anaplastic lymphomas [35].…”
Section: Htlv-i-associated Cutaneous T-cell Lymphoma (Ctcl)mentioning
confidence: 99%
“…Most patients with CTCL are negative for antibodies to the structural proteins of HTLV-I, and thus a causative role for this virus is usually dismissed. However, numerous studies have found HTLV-I-related proviral tax sequence or deleted proviruses in tumor samples from CTCL patients [27][28][29][30][31][32][33][34]. Recently a study on the northeastern coast of Brazil found HTLV-I integrated proviral sequences by southern blot in several mycosis fungoides-like cutaneous lymphomas, and CD30 + largecell anaplastic lymphomas [35].…”
Section: Htlv-i-associated Cutaneous T-cell Lymphoma (Ctcl)mentioning
confidence: 99%
“…Several studies have suggested that infectious agents [12][13][14] or environmental exposures [15][16][17] may play a role in CTCL. While the unusual geographic differences seen in our data could be explained by an environmental or viral exposure, our data neither directly support nor contradict such hypotheses.…”
Section: Commentmentioning
confidence: 99%
“…T cells represent the primary susceptible population in vivo while progenitor cells, monocytes, and dendritic cells have also been reported to be susceptible to infection by HTLV-1 (Ali et al, 1993;Makino et al, 1999) and were hence assessed for their relative binding affinity to HTLV-1. HTLV-1 has been shown to play a role in the pathogenesis of cutaneous T cell lymphoma (Zucker-Franklin, 2001), therefore, vaginal keratinocyte (VK-2) cells were also examined with respect to binding. The P4R5 cell line, a derivative of the epithelial cell line HeLa engineered to express HIV receptor (CD4) and co-receptors (CCR5 and CXCR4) were examined to determine if receptors for HIV-1 also played a role in HTLV-1 binding.…”
Section: Htlv-1 Binding Affinity To Clinically Relevant Cell-typesmentioning
confidence: 99%